Production process of antistatic polyamide fiber
By using specific antistatic agents and anti-ultraviolet agents in nylon fibers, the problems of insufficient anti-static, flame retardant and anti-ultraviolet aging properties of nylon fibers are solved, and its comprehensive performance is significantly improved.
Patent Information
- Application Number
- CN202411545763.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-11
AI Technical Summary
Nylon fibers have insufficient antistatic, flame retardant and ultraviolet aging resistance during use, resulting in shortening of service life, low safety and limited application range.
By preparing a production process for the production of antistatic nylon fibers, the antistatic agent is obtained by reacting grafting from epoxy product 4 and activated carbon fibers. The anti-ultraviolet agent molecule contains benzimidazole, thiol ester, hindered phenol and amide structures.
It significantly improves the antistatic, flame retardant and ultraviolet aging resistance of nylon fibers, extends the service life, and improves the safety and scope of application.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile chemical fiber production, and in particular to a production process of antistatic nylon fiber. Background Art
[0002] As a synthetic fiber, nylon fiber has excellent properties such as corrosion resistance, mildew resistance, high wet strength, high wear resistance, and good elasticity, so it has been widely studied and used. In actual use, nylon fiber has poor light or UV resistance, discolors under sunlight or ultraviolet rays, resulting in varying degrees of degradation and shortening its service life. Nylon fiber is a flammable material, which leads to low safety and limited scope of application. Nylon fiber has poor conductivity and is prone to static electricity accumulation when the air is dry and the ambient humidity is low. When the charge accumulates to a certain level, it will break through the air insulation, generate sparks, form a fire source, and cause a fire.
[0003] In summary, it is important and necessary to solve the problems of nylon fiber's antistatic, flame retardancy and UV aging resistance during use and improve its comprehensive performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a production process of antistatic nylon fiber.
[0005] The purpose of the present invention can be achieved through the following technical solutions: The preparation of the antistatic nylon fiber comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 80-90 parts of polyamide, 2-4 parts of antistatic agent, 0.7-0.9 parts of anti-ultraviolet agent, 0.7-0.9 parts of auxiliary agent, 2.5-3.5 parts of toughening agent and 0.5-0.7 parts of dispersant; the auxiliary agent is antioxidant 168; the toughening agent is maleic anhydride grafted POE (supplier Dongguan Taotao Plastic Raw Materials Co., Ltd.); the dispersant is paraffin; Step S2: adding the raw materials weighed in step S1 into a twin-screw extruder, and melt-blending and extruding them under the conditions of a melt temperature of 200-220° C., a screw speed of 15-25 r / min, and a die temperature of 170-190° C. to obtain a masterbatch; Step S3: melting polyethylene terephthalate through a twin-screw extruder to obtain a polyester melt; then melting polyamide and masterbatch through a twin-screw extruder to obtain a nylon melt; then placing the polyester melt and the nylon melt on a spinneret with a concentric circle skin-core structure for spinning, and then the fiber is cooled, oiled, led out, and then coiled to obtain an antistatic nylon fiber; Furthermore, the melting temperature of polyethylene terephthalate is 250-260°C, the melting temperature of polyamide and masterbatch is 260-270°C, the spinning temperature is 270-280°C, and the winding speed is 3200-3800m / min; the antistatic nylon fiber is a concentric core-skin structure composite fiber with polyester as the inner core material and nylon as the outer skin material, comprising the following raw materials in parts by weight: 30-40 parts of polyethylene terephthalate, 60-70 parts of polyamide, and 3.6-4.8 parts of masterbatch.
[0006] The preparation of the antistatic agent comprises the following steps: Step A1: Add amino-terminated polyether (supplier: Hubei Langbowan Biopharmaceutical Co., Ltd.), potassium carbonate and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add 3-ethoxyacryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly dropwise add the mixed solution b into the mixed solution a in an ice-water bath at 0°C, after the dropwise addition is completed, heat to 40°C, and stir the mixture at a constant temperature for 10 hours to obtain a reaction product 1; Further, the amount ratio of the amino-terminated polyether, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 100-110 mL; the amount ratio of 3-ethoxyacryloyl chloride and dimethyl sulfoxide is 0.2 mol: 60-70 mL; the amount ratio of the mixed solution a and the mixed solution b is 105-115 mL: 65-75 mL; During the reaction of step A1, the amino group of the amino-terminated polyether reacts with 3-ethoxyacryloyl chloride to generate a reaction product 1; Step A2: Add the reaction product 1 to DMF, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4-5 hours to obtain the epoxy product 2; add the epoxy product 2 and DOPO to a flask, start stirring, heat to 90°C, add triphenylphosphine after 10-15 minutes, continue to heat to 150°C, and maintain for 3.5-4 hours to obtain a reaction solution c, cool the reaction solution c to room temperature, then add ethyl acetate to the reaction solution c, let it stand for 48 hours, and filter to obtain the reaction product 3; Further, the usage ratio of the reaction product 1, DMF and 3-chloroperoxybenzoic acid is 0.1 mol: 110-130 mL: 0.2 mol; the usage ratio of the epoxidation product 2, DOPO, triphenylphosphine and ethyl acetate is 0.1 mol: 0.2-0.25 mol: 0.005-0.008 mol: 140-160 mL; During the reaction of step A2, the carbon-carbon double bond in the reaction product 1 is oxidized to an epoxy group to obtain an epoxy product 2; the epoxy group in the epoxy product 2 then reacts with DOPO to generate a hydroxyl-containing reaction product 3; Step A3: epichlorohydrin and the reaction product 3 are added to methanol, trimethylamine is added under stirring, and the mixture is refluxed and stirred at 70-80° C. for 3-4 hours to obtain a ring-opening product; the ring-opening product is then added to a sodium hydroxide solution and stirred at room temperature for 5 hours, and then extracted and distilled to obtain an epoxy product 4; Furthermore, the dosage ratio of epichlorohydrin, reaction product 3, methanol, and trimethylamine is 0.2 mol: 0.1 mol: 160-170 mL: 0.01-0.015 mol; the dosage ratio of the ring-opening product and the sodium hydroxide solution is 3-4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%; During the reaction of step A3, the hydroxyl group of the reaction product 3 is ring-opened with epichlorohydrin to obtain a ring-opened product; the ring-opened product is ring-closed in a sodium hydroxide solution to obtain an epoxy product 4 containing an epoxy group; Step A4: placing the carbon fiber in acetone, refluxing and stirring at 70°C for 48h, then washing with deionized water and drying at 80°C for 12h to obtain pretreated carbon fiber; then placing the pretreated carbon fiber in a Michaelis acid solution, stirring at 30°C for 3h, then washing with acetone and drying at 80°C for 6-8h to obtain activated carbon fiber; adding the above-mentioned epoxy product 4, activated carbon fiber and pyridine to DMF, starting stirring and introducing nitrogen, stirring and reacting at 40-50°C in a nitrogen atmosphere for 36-40h to obtain an antistatic agent; Further, the usage ratio of carbon fiber and acetone is 5-6 g: 80-90 mL; the usage ratio of pretreated carbon fiber and Michaelis acid solution is 1-1.5 g: 100-110 mL, and the concentration of Michaelis acid solution is 0.025 g / mL; the usage ratio of epoxy product 4, activated carbon fiber, pyridine and DMF is 6-10 g: 1-3 g: 0.1-0.3 g: 180-200 mL; During the reaction of step A4, the sizing agent on the surface of the carbon fiber is removed after heating in acetone, and then the carbon fiber is activated in a Michaelis acid solution to obtain a carbon fiber containing carboxyl groups on the surface, i.e., activated carbon fiber; the carboxyl groups in the activated carbon fiber react with the epoxy groups of the epoxy product 4, and the epoxy product 4 is grafted onto the carbon fiber to obtain an antistatic agent.
[0007] The preparation of the anti-ultraviolet agent comprises the following steps: Step B1: Add N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF into a high-pressure reactor, and stir the reaction at 5-10 MPa and 100-110° C. for 8-9 hours to obtain a reaction product a; Further, the usage ratio of N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF is 0.1 mol: 0.1 mol: 0.015-0.020 mol: 75-85 mL; During the reaction of step B1, the amino group of N-(3'-propylamino)-2-pyrrolidone undergoes a dehydrochlorination coupling reaction with 2-nitro-3-chloro-benzamide to generate a reaction product a; Step B2: Add the reaction product a and toluene into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5h to obtain the reaction product b; Further, the usage ratio of the reaction product a, toluene and sodium dithionite is 0.1 mol: 90-100 mL: 0.1-0.15 mol; During the reaction of step B2, the nitro group of the reaction product a is reduced to an amino group, thereby obtaining a reaction product b containing an amino group; Step B3: Add the reaction product b, carbon disulfide and potassium hydroxide into ethanol, start stirring, then add 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, stir and react at 35-40° C. for 24 hours to obtain the reaction product c; Further, the amount ratio of the reaction product b, carbon disulfide, potassium hydroxide, ethanol and 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate is 0.1 mol: 0.1-0.15 mol: 0.002-0.0025 mol: 130-150 mL: 0.001-0.0012 mol, and the volume fraction of ethanol is 95%; During the reaction of step B3, under the catalysis of 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, the reaction product b reacts with carbon disulfide to generate a reaction product c having a mercaptoimidazole structure; Step B4: Add the reaction product c and triethylamine into a flask, start stirring, add tetrahydrofuran to obtain a mixed solution 1, slowly add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride to the mixed solution 1 in an ice-water bath, after the addition is complete, heat to 40° C., stir to react for 3-4 hours, extract, dry and distill to obtain an anti-ultraviolet agent; Further, the usage ratio of the reaction product c, triethylamine, tetrahydrofuran and 3,5-di-tert-butyl-4-hydroxybenzoyl chloride is 0.1 mol: 0.01-0.015 mol: 150-160 mL: 0.12-0.15 mol; During the reaction of step B4, the thiol group of the reaction product c reacts with 3,5-di-tert-butyl-4-hydroxybenzoyl chloride to generate a thiol-containing UV inhibitor.
[0008] Beneficial effects of the present invention: The present invention discloses a production process of antistatic nylon fiber; the antistatic agent used in the synthesis process of the masterbatch used to prepare the antistatic nylon fiber is obtained by reaction grafting of the epoxy product 4 and the carbon fiber containing carboxyl groups on the surface after activation, and the epoxy product 4 molecule includes a polyether structure, an amide structure and a DOPO structure. The amide structure enhances the dispersion compatibility of the antistatic agent in the masterbatch; the molecular chain of the polyether structure contains a large number of ether bonds, which can associate with water molecules through hydrogen bonds to reduce the surface resistance of the fiber, and the polyether has good heat resistance and can stably play an antistatic role; the DOPO structure can dehydrate and degrade the polymer surface to form a carbon layer when the matrix burns, and the phosphorus-containing derivatives produced at the same time cover the polymer surface, isolate the combustible gas, block the heat transfer, form a physical shield, and play a flame retardant role; carbon fiber is a conductive filler, which can form a conductive path in the antistatic nylon fiber and synergistically play an antistatic role with the polyether structure; therefore, the antistatic agent improves the antistatic and flame retardant properties of the antistatic nylon fiber.
[0009] The anti-ultraviolet agent used in the synthesis process of the masterbatch used for preparing the anti-static nylon fiber includes a benzimidazole structure, a thioester structure, a hindered phenol structure and an amide structure in the molecule; the aromatic benzene ring and the imidazole ring in the benzimidazole structure form multiple conjugated systems, which can absorb ultraviolet rays and convert high-energy ultraviolet light into heat energy and then release it, thereby preventing the fiber from being damaged by ultraviolet rays and degrading; after the thioester structure is introduced, the lone electron pair of the sulfur atom reduces the rigid structure of the benzimidazole, increases the relative molecular weight of the compound, improves its stability, and enhances ultraviolet absorption; the hindered phenol structure destroys the free radical auto-oxidation chain reaction through proton donation, thereby exerting an antioxidant effect, and synergistically exerts an anti-ultraviolet aging effect with the benzimidazole structure and the thioester structure, and after the hindered phenol is introduced, the relative molecular weight of the compound is further increased, and the stability of the anti-ultraviolet agent is further improved; the amide structure is the same as the polyamide structure, which enhances its dispersion compatibility in the masterbatch, so that the anti-static nylon fiber has excellent anti-ultraviolet aging. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0011] Embodiment 1: An antistatic agent, the preparation of which comprises the following steps: Step A1: Add amino-terminated polyether (supplier: Hubei Langbowan Biopharmaceutical Co., Ltd.), potassium carbonate and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add 3-ethoxyacryloyl chloride to dimethyl sulfoxide to obtain a mixed solution b, slowly dropwise add the mixed solution b into the mixed solution a under a 0°C ice-water bath, after the dropwise addition is completed, heat to 40°C, and stir at a constant temperature for 10 hours to obtain a reaction product 1; the amount ratio of amino-terminated polyether, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 100 mL; the amount ratio of 3-ethoxyacryloyl chloride and dimethyl sulfoxide is 0.2 mol: 60 mL; the amount ratio of mixed solution a to mixed solution b is 105 mL: 65 mL; Step A2: Add the reaction product 1 to DMF, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4 hours to obtain the epoxy product 2; add the epoxy product 2 and DOPO to a flask, start stirring, heat to 90°C, add triphenylphosphine after 10 minutes, continue to heat to 150°C, keep for 3.5 hours to obtain a reaction solution c, cool the reaction solution c to room temperature, then add ethyl acetate to the reaction solution c, let it stand for 48 hours, and filter to obtain the reaction product 3; the amount ratio of the reaction product 1, DMF and 3-chloroperoxybenzoic acid is 0.1 mol: 110 mL: 0.2 mol; the amount ratio of the epoxy product 2, DOPO, triphenylphosphine and ethyl acetate is 0.1 mol: 0.2 mol: 0.005 mol: 140 mL; Step A3: Add epichlorohydrin and reaction product 3 to methanol, add trimethylamine under stirring, and react under reflux stirring at 70°C for 3 hours to obtain a ring-opening product; then add the ring-opening product to a sodium hydroxide solution, and stir at room temperature for 5 hours, extract and distill to obtain an epoxy product 4; the amount ratio of epichlorohydrin, reaction product 3, methanol, and trimethylamine is 0.2 mol: 0.1 mol: 160 mL: 0.01 mol; the amount ratio of the ring-opening product and the sodium hydroxide solution is 3 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%; Step A4: Place the carbon fiber in acetone, reflux and stir at 70°C for 48 hours, then wash with deionized water and dry at 80°C for 12 hours to obtain pretreated carbon fiber; then place the pretreated carbon fiber in a Michaelis acid solution, stir at 30°C for 3 hours, then wash with acetone and dry at 80°C for 6 hours to obtain activated carbon fiber; add the above-mentioned epoxy product 4, activated carbon fiber, and pyridine to DMF, start stirring and introduce nitrogen, and stir the reaction at 40°C in a nitrogen atmosphere for 36 hours to obtain an antistatic agent; the amount ratio of carbon fiber to acetone is 5g:80mL; the amount ratio of pretreated carbon fiber to Michaelis acid solution is 1:100mL, and the concentration of Michaelis acid solution is 0.025g / mL; the amount ratio of epoxy product 4, activated carbon fiber, pyridine and DMF is 6g:1g:0.1g:180mL.
[0012] Embodiment 2: An antistatic agent, the preparation of which comprises the following steps: Step A1: amino-terminated polyether (supplier: Hubei Langbowan Biopharmaceutical Co., Ltd.), potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then 3-ethoxyacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b. The mixed solution b is slowly added dropwise into the mixed solution a in an ice water bath at 0°C. After the addition is completed, the temperature is raised to 40°C, and the reaction is stirred at a constant temperature for 10 hours to obtain a reaction product 1. The amount ratio of amino-terminated polyether, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 105 mL; the amount ratio of 3-ethoxyacryloyl chloride and dimethyl sulfoxide is 0.2 mol: 65 mL; the amount ratio of mixed solution a to mixed solution b is 110 mL: 70 mL; Step A2: Add the reaction product 1 to DMF, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4.5 hours to obtain the epoxy product 2; add the epoxy product 2 and DOPO to a flask, start stirring, heat to 90°C, add triphenylphosphine after 12 minutes, continue to heat to 150°C, keep for 3.7 hours to obtain the reaction solution c, cool the reaction solution c to room temperature, then add ethyl acetate to the reaction solution c, let it stand for 48 hours, and filter to obtain the reaction product 3; the amount ratio of the reaction product 1, DMF and 3-chloroperoxybenzoic acid is 0.1 mol: 120 mL: 0.2 mol; the amount ratio of the epoxy product 2, DOPO, triphenylphosphine and ethyl acetate is 0.1 mol: 0.22 mol: 0.006 mol: 150 mL; Step A3: Add epichlorohydrin and reaction product 3 to methanol, add trimethylamine under stirring, and reflux and stir at 75°C for 3.5 hours to obtain a ring-opening product; then add the ring-opening product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain an epoxy product 4; the amount ratio of epichlorohydrin, reaction product 3, methanol and trimethylamine is 0.2 mol: 0.1 mol: 165 mL: 0.013 mol; the amount ratio of the ring-opening product and the sodium hydroxide solution is 3.5 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%; Step A4: placing the carbon fiber in acetone, refluxing and stirring at 70°C for 48h, then washing with deionized water and drying at 80°C for 12h to obtain pretreated carbon fiber; then placing the pretreated carbon fiber in a Michaelis acid solution, stirring at 30°C for 3h, then washing with acetone and drying at 80°C for 7h to obtain activated carbon fiber; adding the above-mentioned epoxy product 4, activated carbon fiber, and pyridine to DMF, starting stirring and introducing nitrogen, stirring and reacting at 45°C in a nitrogen atmosphere for 38h to obtain an antistatic agent; the amount ratio of carbon fiber to acetone is 5.5g:85mL; the amount ratio of pretreated carbon fiber to Michaelis acid solution is 1.2g:105mL, and the concentration of Michaelis acid solution is 0.025g / mL; the amount ratio of epoxy product 4, activated carbon fiber, pyridine and DMF is 8g:2g:0.2g:190mL.
[0013] Embodiment 3: An antistatic agent, the preparation of which comprises the following steps: Step A1: amino-terminated polyether (supplier: Hubei Langbowan Biopharmaceutical Co., Ltd.), potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then 3-ethoxyacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b. The mixed solution b is slowly added dropwise into the mixed solution a in an ice water bath at 0°C. After the addition is completed, the mixture is heated to 40°C and stirred at a constant temperature for 10 hours to obtain a reaction product 1. The amount ratio of amino-terminated polyether, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 110 mL; the amount ratio of 3-ethoxyacryloyl chloride and dimethyl sulfoxide is 0.2 mol: 70 mL; the amount ratio of mixed solution a to mixed solution b is 115 mL: 75 mL; Step A2: Add the reaction product 1 to DMF, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 5 hours to obtain the epoxy product 2; add the epoxy product 2 and DOPO to a flask, start stirring, heat to 90°C, add triphenylphosphine after 15 minutes, continue to heat to 150°C, keep for 4 hours to obtain a reaction solution c, cool the reaction solution c to room temperature, then add ethyl acetate to the reaction solution c, let it stand for 48 hours, and filter to obtain the reaction product 3; the amount ratio of the reaction product 1, DMF and 3-chloroperoxybenzoic acid is 0.1 mol: 130 mL: 0.2 mol; the amount ratio of the epoxy product 2, DOPO, triphenylphosphine and ethyl acetate is 0.1 mol: 0.25 mol: 0.008 mol: 160 mL; Step A3: Add epichlorohydrin and reaction product 3 to methanol, add trimethylamine under stirring, and reflux and stir at 80°C for 4 hours to obtain a ring-opening product; then add the ring-opening product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain an epoxy product 4; the amount ratio of epichlorohydrin, reaction product 3, methanol and trimethylamine is 0.2 mol: 0.1 mol: 170 mL: 0.015 mol; the amount ratio of the ring-opening product and the sodium hydroxide solution is 4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%; Step A4: placing the carbon fiber in acetone, reflux stirring at 70°C for 48h, then washing with deionized water and drying at 80°C for 12h to obtain pretreated carbon fiber; then placing the pretreated carbon fiber in a Michaelis acid solution, stirring at 30°C for 3h, then washing with acetone and drying at 80°C for 8h to obtain activated carbon fiber; adding the above-mentioned epoxy product 4, activated carbon fiber, and pyridine to DMF, starting stirring and introducing nitrogen, stirring and reacting at 50°C in a nitrogen atmosphere for 40h to obtain an antistatic agent; the amount ratio of carbon fiber to acetone is 6g:90mL; the amount ratio of pretreated carbon fiber to Michaelis acid solution is 1.5g:110mL, and the concentration of Michaelis acid solution is 0.025g / mL; the amount ratio of epoxy product 4, activated carbon fiber, pyridine and DMF is 10g:3g:0.3g:200mL.
[0014] Embodiment 4: A kind of anti-ultraviolet agent, its preparation comprises the following steps: Step B1: Add N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF into a high-pressure reactor, stir and react at 5 MPa and 100° C. for 8 h to obtain reaction product a; the amount ratio of N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF is 0.1 mol: 0.1 mol: 0.015 mol: 75 mL; Step B2: Add the reaction product a and toluene into a three-necked flask, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1 hour to obtain the reaction product b; the amount ratio of the reaction product a, toluene and sodium dithionite is 0.1 mol:90 mL:0.1 mol; Step B3: adding the reaction product b, carbon disulfide and potassium hydroxide to ethanol, starting stirring, and then adding 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, stirring and reacting at 35° C. for 24 hours to obtain a reaction product c; the amount ratio of the reaction product b, carbon disulfide, potassium hydroxide, ethanol and 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate is 0.1 mol: 0.1 mol: 0.002 mol: 130 mL: 0.001 mol, and the volume fraction of ethanol is 95%; Step B4: Add the reaction product c and triethylamine into a flask, start stirring, add tetrahydrofuran to obtain a mixed solution 1, slowly add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride to the mixed solution 1 in an ice-water bath, after the addition is complete, heat to 40°C, stir to react for 3 hours, extract, dry and distill to obtain an anti-ultraviolet agent; the amount ratio of the reaction product c, triethylamine, tetrahydrofuran and 3,5-di-tert-butyl-4-hydroxybenzoyl chloride is 0.1 mol: 0.01 mol: 150 mL: 0.12 mol.
[0015] Embodiment 5: A kind of anti-ultraviolet agent, its preparation comprises the following steps: Step B1: Add N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF into a high-pressure reactor, stir and react at 7 MPa and 105° C. for 8.5 h to obtain reaction product a; the amount ratio of N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF is 0.1 mol: 0.1 mol: 0.017 mol: 80 mL; Step B2: Add the reaction product a and toluene into a three-necked flask, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.2h to obtain the reaction product b; the amount ratio of the reaction product a, toluene and sodium dithionite is 0.1mol:95mL:0.12mol; Step B3: adding the reaction product b, carbon disulfide and potassium hydroxide to ethanol, starting stirring, and then adding 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, stirring and reacting at 37° C. for 24 hours to obtain a reaction product c; the amount ratio of the reaction product b, carbon disulfide, potassium hydroxide, ethanol and 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate is 0.1 mol: 0.12 mol: 0.0022 mol: 140 mL: 0.0011 mol, and the volume fraction of ethanol is 95%; Step B4: Add the reaction product c and triethylamine to a flask, start stirring, add tetrahydrofuran to obtain a mixed solution 1, slowly add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride to the mixed solution 1 in an ice-water bath, after the addition is complete, heat to 40°C, stir to react for 3.5 hours, extract, dry and distill to obtain an anti-ultraviolet agent; the dosage ratio of the reaction product c, triethylamine, tetrahydrofuran and 3,5-di-tert-butyl-4-hydroxybenzoyl chloride is 0.1 mol: 0.012 mol: 155 mL: 0.13 mol.
[0016] Embodiment 6: A kind of anti-ultraviolet agent, its preparation comprises the following steps: Step B1: Add N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF into a high pressure reactor, stir and react at 10 MPa and 110° C. for 9 h to obtain reaction product a; the amount ratio of N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF is 0.1 mol: 0.1 mol: 0.020 mol: 85 mL; Step B2: Add the reaction product a and toluene into a three-necked flask, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.5 hours to obtain the reaction product b; the amount ratio of the reaction product a, toluene and sodium dithionite is 0.1 mol: 100 mL: 0.15 mol; Step B3: adding the reaction product b, carbon disulfide and potassium hydroxide to ethanol, starting stirring, and then adding 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, stirring and reacting at 40° C. for 24 hours to obtain a reaction product c; the amount ratio of the reaction product b, carbon disulfide, potassium hydroxide, ethanol and 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate is 0.1 mol: 0.15 mol: 0.0025 mol: 150 mL: 0.0012 mol, and the volume fraction of ethanol is 95%; Step B4: Add the reaction product c and triethylamine to a flask, start stirring, add tetrahydrofuran to obtain a mixed solution 1, slowly add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride to the mixed solution 1 in an ice-water bath, after the addition is complete, heat to 40°C, stir to react for 4 hours, extract, dry and distill to obtain an anti-ultraviolet agent; the dosage ratio of the reaction product c, triethylamine, tetrahydrofuran and 3,5-di-tert-butyl-4-hydroxybenzoyl chloride is 0.1 mol: 0.015 mol: 160 mL: 0.15 mol.
[0017] Embodiment 7: The preparation of the antistatic nylon fiber comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 80 parts of polyamide, 2 parts of the antistatic agent obtained in Example 1, 0.7 parts of the anti-ultraviolet agent obtained in Example 4, 0.7 parts of an auxiliary agent, 2.5 parts of a toughening agent, and 0.5 parts of a dispersant; the auxiliary agent is antioxidant 168; the toughening agent is maleic anhydride grafted POE (supplier Dongguan Taotao Plastic Raw Materials Co., Ltd.); the dispersant is paraffin; Step S2: adding the raw materials weighed in step S1 into a twin-screw extruder, and melt-blending and extruding them at a melt temperature of 200° C., a screw speed of 15 r / min, and a die temperature of 170° C. to obtain a masterbatch; Step S3: melting polyethylene terephthalate through a twin-screw extruder to obtain a polyester melt; then melting polyamide and masterbatch through a twin-screw extruder to obtain a nylon melt; then placing the polyester melt and the nylon melt on a spinneret with a concentric skin-core structure for spinning, and then the fiber is cooled, oiled, and then taken up to obtain an antistatic nylon fiber; the melting temperature of polyethylene terephthalate is 250°C, the melting temperature of polyamide and masterbatch is 260°C, the spinning temperature is 270°C, and the winding speed is 3200m / min; the antistatic nylon fiber is a concentric skin-core structure composite fiber with polyester as the inner ring core material and nylon as the outer ring skin material, comprising the following raw materials in parts by weight: 30 parts of polyethylene terephthalate, 60 parts of polyamide, and 3.6 parts of masterbatch.
[0018] Embodiment 8: The preparation of the antistatic nylon fiber comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 85 parts of polyamide, 3 parts of the antistatic agent obtained in Example 2, 0.8 parts of the anti-ultraviolet agent obtained in Example 5, 0.8 parts of an auxiliary agent, 3.0 parts of a toughening agent, and 0.6 parts of a dispersant; the auxiliary agent is an antioxidant 168; the toughening agent is maleic anhydride grafted POE (supplier Dongguan Taotao Plastic Raw Materials Co., Ltd.); the dispersant is paraffin; Step S2: adding the raw materials weighed in step S1 to a twin-screw extruder, and melt-blending and extruding at a melt temperature of 210° C., a screw speed of 20 r / min, and a die temperature of 180° C. to obtain a masterbatch; Step S3: melting polyethylene terephthalate through a twin-screw extruder to obtain a polyester melt; then melting polyamide and masterbatch through a twin-screw extruder to obtain a nylon melt; then placing the polyester melt and the nylon melt on a spinneret with a concentric skin-core structure for spinning, and then the fiber is cooled, oiled, and then taken up to obtain an antistatic nylon fiber; the melting temperature of polyethylene terephthalate is 255°C, the melting temperature of polyamide and masterbatch is 265°C, the spinning temperature is 275°C, and the winding speed is 3500m / min; the antistatic nylon fiber is a concentric skin-core structure composite fiber with polyester as the inner ring core material and nylon as the outer ring skin material, comprising the following raw materials in parts by weight: 35 parts of polyethylene terephthalate, 65 parts of polyamide, and 4.2 parts of masterbatch.
[0019] Embodiment 9: The preparation of the antistatic nylon fiber comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 90 parts of polyamide, 4 parts of the antistatic agent obtained in Example 3, 0.9 parts of the anti-ultraviolet agent obtained in Example 6, 0.9 parts of an auxiliary agent, 3.5 parts of a toughening agent, and 0.7 parts of a dispersant; the auxiliary agent is an antioxidant 168; the toughening agent is maleic anhydride grafted POE (supplier Dongguan Taotao Plastic Raw Materials Co., Ltd.); the dispersant is paraffin; Step S2: adding the raw materials weighed in step S1 into a twin-screw extruder, and melt-blending and extruding at a melt temperature of 220° C., a screw speed of 25 r / min, and a die temperature of 190° C. to obtain a masterbatch; Step S3: melting polyethylene terephthalate through a twin-screw extruder to obtain a polyester melt; then melting polyamide and masterbatch through a twin-screw extruder to obtain a nylon melt; then placing the polyester melt and the nylon melt on a spinneret with a concentric skin-core structure for spinning, and then the fiber is cooled, oiled, and then taken up to obtain an antistatic nylon fiber; the melting temperature of polyethylene terephthalate is 260°C, the melting temperature of polyamide and masterbatch is 270°C, the spinning temperature is 280°C, and the winding speed is 3800m / min; the antistatic nylon fiber is a concentric skin-core structure composite fiber with polyester as the inner ring core material and nylon as the outer ring skin material, comprising the following raw materials in parts by weight: 40 parts of polyethylene terephthalate, 70 parts of polyamide, and 4.8 parts of masterbatch.
[0020] Comparative Example 1: This comparative example is commercially available ordinary nylon fiber.
[0021] Comparative Example 2: Compared with Example 9, the antistatic agent is replaced by reaction product 3, that is, carbon nanotubes are not introduced, and the rest is exactly the same as Example 9 to obtain antistatic nylon fiber.
[0022] Comparative Example 3: Compared with Example 9, the anti-ultraviolet agent is replaced with reaction product c, that is, hindered phenol and thiol ester structure are not introduced, and the rest is exactly the same as Example 9 to obtain antistatic nylon fiber.
[0023] The antistatic nylon fiber prepared by the present invention is further tested for its effect, and the test results are as follows.
[0024] In order to test the antistatic nylon fiber prepared by the present invention, the breaking strength and breaking elongation were measured according to GB / T14344-2022 "Test method for tensile properties of chemical fiber filaments"; the ultraviolet aging method was as follows: the antistatic nylon fibers obtained in Examples 7-9 and Comparative Examples 1-3 were placed under 0.89 W / m 2 After aging at 50°C and aging time of 7 days, the retention rate of breaking strength and elongation at break were determined according to GB / T14344-2022; the surface resistance was tested according to the parallel electrode sensing method of ASTM standard D-257; the limiting oxygen index was determined according to GB / T5454-1997 "Textile Combustion Performance Test Oxygen Index Method", and the results are recorded in Table 1; Table 1: Performance test results
[0025] According to the data in Table 1, compared with Example 1, Example 7, Example 8 and Example 9, it can be seen that the antistatic nylon fiber of the present invention has good anti-ultraviolet aging, antistatic and flame retardancy compared with commercially available nylon fibers; compared with Example 2, Example 9 shows that the use of a synthetic antistatic agent, the introduction of carbon fiber, and the synergistic antistatic effect with polyether significantly improve the antistatic property of the antistatic nylon fiber; compared with Example 3, Example 9 shows that the use of a synthetic anti-ultraviolet agent, the introduction of hindered phenol and thiol ester structures, and the synergistic effect with the benzimidazole structure are more conducive to the improvement of the anti-ultraviolet aging performance.
[0026] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A production process for antistatic nylon fiber, characterized in that: The steps include: Step S1: Weigh the following raw materials in parts by weight: 80-90 parts of polyamide, 2-4 parts of antistatic agent, 0.7-0.9 parts of anti-ultraviolet agent, 0.7-0.9 parts of auxiliary agent, 2.5-3.5 parts of toughening agent and 0.5-0.7 parts of dispersant; the auxiliary agent is antioxidant 168; the toughening agent is maleic anhydride grafted POE; the dispersant is paraffin; Step S2: adding the raw materials weighed in step S1 into a twin-screw extruder, and melt-blending and extruding them under the conditions of a melt temperature of 200-220° C., a screw speed of 15-25 r / min, and a die temperature of 170-190° C. to obtain a masterbatch; Step S3: melting polyethylene terephthalate through a twin-screw extruder to obtain a polyester melt; then melting polyamide and masterbatch through a twin-screw extruder to obtain a nylon melt; then placing the polyester melt and the nylon melt on a spinneret with a concentric circle skin-core structure for spinning, and then the fiber is cooled, oiled, and then coiled to obtain an antistatic nylon fiber.
2. The production process of an antistatic nylon fiber according to claim 1, characterized in that: In step S3, the melting temperature of polyethylene terephthalate is 250-260°C; the melting temperature of polyamide and masterbatch is 260-270°C; the spinning temperature is 270-280°C; the winding speed is 3200-3800m / min; the antistatic nylon fiber is a concentric core-skin structure composite fiber with polyester as the inner core material and nylon as the outer skin material, comprising the following raw materials in parts by weight: 30-40 parts of polyethylene terephthalate, 60-70 parts of polyamide, and 3.6-4.8 parts of masterbatch.
3. The production process of an antistatic nylon fiber according to claim 1, characterized in that: The preparation of the antistatic agent comprises the following steps: Step A1: Add amino-terminated polyether, potassium carbonate and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add 3-ethoxyacryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly dropwise add the mixed solution b into the mixed solution a in an ice-water bath at 0° C. After the dropwise addition is completed, the temperature is raised to 40° C., and the reaction is stirred at a constant temperature for 10 hours to obtain a reaction product 1; Step A2: Add the reaction product 1 to DMF, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4-5 hours to obtain the epoxy product 2; add the epoxy product 2 and DOPO to a flask, start stirring, heat to 90°C, add triphenylphosphine after 10-15 minutes, continue to heat to 150°C, and maintain for 3.5-4 hours to obtain a reaction solution c, cool the reaction solution c to room temperature, then add ethyl acetate to the reaction solution c, let it stand for 48 hours, and filter to obtain the reaction product 3; Step A3: epichlorohydrin and the reaction product 3 are added to methanol, trimethylamine is added under stirring, and the mixture is refluxed and stirred at 70-80° C. for 3-4 hours to obtain a ring-opening product; the ring-opening product is then added to a sodium hydroxide solution and stirred at room temperature for 5 hours, and then extracted and distilled to obtain an epoxy product 4; Step A4: Place the carbon fiber in acetone, reflux and stir at 70°C for 48 hours, then wash with deionized water and dry at 80°C for 12 hours to obtain pretreated carbon fiber; then place the pretreated carbon fiber in a Michaelis acid solution, stir at 30°C for 3 hours, then wash with acetone and dry at 80°C for 6-8 hours to obtain activated carbon fiber; add the above-mentioned epoxy product 4, activated carbon fiber and pyridine to DMF, start stirring and introduce nitrogen, and stir the reaction at 40-50°C in a nitrogen atmosphere for 36-40 hours to obtain an antistatic agent.
4. The production process of antistatic nylon fiber according to claim 3, characterized in that: In step A1, the amount ratio of the amino-terminated polyether, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 100-110 mL; the amount ratio of 3-ethoxyacryloyl chloride and dimethyl sulfoxide is 0.2 mol: 60-70 mL; the amount ratio of the mixed solution a and the mixed solution b is 105-115 mL: 65-75 mL.
5. The production process of antistatic nylon fiber according to claim 3, characterized in that: In step A2, the usage ratio of the reaction product 1, DMF and 3-chloroperbenzoic acid is 0.1 mol: 110-130 mL: 0.2 mol; the usage ratio of the epoxidation product 2, DOPO, triphenylphosphine and ethyl acetate is 0.1 mol: 0.2-0.25 mol: 0.005-0.008 mol: 140-160 mL.
6. The production process of antistatic nylon fiber according to claim 3, characterized in that: In step A3, the usage ratio of epichlorohydrin, reaction product 3, methanol and trimethylamine is 0.2 mol: 0.1 mol: 160-170 mL: 0.01-0.015 mol; the usage ratio of the ring-opening product and the sodium hydroxide solution is 3-4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%.
7. The production process of antistatic nylon fiber according to claim 3, characterized in that: In step A4, the usage ratio of carbon fiber and acetone is 5-6 g: 80-90 mL; the usage ratio of pretreated carbon fiber and Michaelis acid solution is 1-1.5 g: 100-110 mL, and the concentration of Michaelis acid solution is 0.025 g / mL; the usage ratio of epoxy product 4, activated carbon fiber, pyridine and DMF is 6-10 g: 1-3 g: 0.1-0.3 g: 180-200 mL.
8. The production process of antistatic nylon fiber according to claim 1, characterized in that: The preparation of the anti-ultraviolet agent comprises the following steps: Step B1: Add N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF into a high-pressure reactor, and stir the reaction at 5-10 MPa and 100-110° C. for 8-9 hours to obtain a reaction product a; Step B2: Add the reaction product a and toluene into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5h to obtain the reaction product b; Step B3: Add the reaction product b, carbon disulfide and potassium hydroxide into ethanol, start stirring, then add 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, stir and react at 35-40° C. for 24 hours to obtain the reaction product c; Step B4: Add the reaction product c and triethylamine into a flask, start stirring, add tetrahydrofuran to obtain a mixed solution 1, slowly add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride to the mixed solution 1 in an ice-water bath, after the addition is complete, heat to 40°C, stir to react for 3-4 hours, and obtain an anti-ultraviolet agent through extraction, drying and distillation.
9. The production process of antistatic nylon fiber according to claim 8, characterized in that: In step B1, the amount ratio of N-(3'-propylamino)-2-pyrrolidone, 2-nitro-3-chloro-benzamide, sodium hydroxide and DMF is 0.1 mol: 0.1 mol: 0.015-0.020 mol: 75-85 mL; in step B2, the amount ratio of reaction product a, toluene and sodium dithionite is 0.1 mol: 90-100 mL: 0.1-0.15 mol.
10. The production process of antistatic nylon fiber according to claim 8, characterized in that: In step B3, the amount ratio of reaction product b, carbon disulfide, potassium hydroxide, ethanol and 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate is 0.1 mol: 0.1-0.15 mol: 0.002-0.0025 mol: 130-150 mL: 0.001-0.0012 mol, and the volume fraction of ethanol is 95%; in step B4, the amount ratio of reaction product c, triethylamine, tetrahydrofuran and 3,5-di-tert-butyl-4-hydroxybenzoyl chloride is 0.1 mol: 0.01-0.015 mol: 150-160 mL: 0.12-0.15 mol.
Citation Information
Cited By
Polyamide slice for transparent fishing net and preparation method thereof
CN120082194A
Wear-resistant rabbit hair-like fiber and preparation method thereof
CN120311346A
Antistatic polyester fiber and preparation method thereof
CN120905799A